Putative physiological mechanisms underlying tDCS analgesic effects - Knotkova, Helena; Nitsche, Michael A.; Cruciani, Ricardo A. (Frontiers in Human Neuroscience, 2013)
Transcranial direct current stimulation (tDCS) is a non-invasive neuromodulation technique that induces changes in excitability, and activation of brain neurons and neuronal circuits. It has been observed that beyond regional effects under the electrodes, tDCS also alters activity of remote interconnected cortical and subcortical areas. This makes the tDCS stimulation technique potentially promising for modulation of pain syndromes. Indeed, utilizing specific montages, tDCS resulted in analgesic effects in experimental settings, as well as in post-operative acute pain and chronic pain syndromes. The promising evidence of tDCS-induced analgesic effects raises the challenging and complex question of potential physiologic mechanisms that underlie/mediate the accomplished pain relief. Here we present hypotheses on how the specific montages and targets for stimulation may affect the pain processing network.